Consumption of Tropospheric Levels of Methyl Bromide by C(1) Compound-Utilizing Bacteria and Comparison to Saturation Kinetics - Goodwin, Kelly D. (American Society for Microbiology, 2001)
Pure cultures of methylotrophs and methanotrophs are known to oxidize methyl bromide (MeBr); however, their ability to oxidize tropospheric concentrations (parts per trillion by volume [pptv]) has not been tested. Methylotrophs and methanotrophs were able to consume MeBr provided at levels that mimicked the tropospheric mixing ratio of MeBr (12 pptv) at equilibrium with surface waters (≈2 pM). Kinetic investigations using picomolar concentrations of MeBr in a continuously stirred tank reactor (CSTR) were performed using strain IMB-1 and Leisingeria methylohalidivorans strain MB2(T) — terrestrial and marine methylotrophs capable of halorespiration. First-order uptake of MeBr with no indication of threshold was observed for both strains. Strain MB2(T) displayed saturation kinetics in batch experiments using micromolar MeBr concentrations, with an apparent K(s) of 2.4 μM MeBr and a V(max) of 1.6 nmol h(−1) (10(6) cells)(−1). Apparent first-order degradation rate constants measured with the CSTR were consistent with kinetic parameters determined in batch experiments, which used 35- to 1 × 10(7)-fold-higher MeBr concentrations. Ruegeria algicola (a phylogenetic relative of strain MB2(T)), the common heterotrophs Escherichia coli and Bacillus pumilus, and a toluene oxidizer, Pseudomonas mendocina KR1, were also tested. These bacteria showed no significant consumption of 12 pptv MeBr; thus, the ability to consume ambient mixing ratios of MeBr was limited to C(1) compound-oxidizing bacteria in this study. Aerobic C(1) bacteria may provide model organisms for the biological oxidation of tropospheric MeBr in soils and waters.